Direct benefits from choosing a virgin male in the European grapevine moth, Lobesia botrana. (April 2016) - Muller, Karen; Arenas, Laura; Thiéry, Denis; Moreau, Jérôme
Abstract : In Lepidoptera, male investment in the ejaculate usually declines over consecutive matings, a depletion that could have profound consequences for female reproductive output. Since successive matings can affect the ability of males to provide phenotypic benefits, there may be strong selection for females to discriminate between males with different mating experience. The aim of our study was to determine whether monandrous females of the European grapevine moth, Lobesia botrana, are able to discriminate between males of different quality based on their mating experience in order to maximize direct benefits (by receiving large spermatophores from virgin males) and minimize mating costs (by avoiding low-quality nonvirgin males). Nonvirgin males produced spermatophores five times smaller than those of virgin males; consequently, mating with nonvirgin males significantly reduced female fecundity and increased their motivation to remate. In a mate preference experiment, we found that females were more likely to mate with virgin males and more frequently rejected nonvirgin mates. Moreover, nonvirgin males required more time to achieve mating than virgin males. Our results suggest that females are able to discriminate between males with different mating experience, and prefer virgin males, thereby maximizing direct benefits associated with receiving large spermatophores. Highlights: We examined the effect of male mating experience on female reproduction. Females mated with nonvirgin males suffered a reduction in lifetime fecundity. Females mated with nonvirgin males exhibited an increased motivation to remate. Females preferentially mated with virgin males in order to maximize direct benefits.